2014
DOI: 10.1186/2045-7022-4-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two oral probiotic preparations in a randomized crossover trial highlights a potentially beneficial effect of Lactobacillus paracasei NCC2461 in patients with allergic rhinitis

Abstract: BackgroundThere is promising but conflicting evidence to recommend the addition of probiotics to foods for prevention and treatment of allergy. Based on previous studies with fermented milk containing Lactobacillus paracasei NCC2461, we aimed to compare the effect of a powder form of the latter probiotic with the effect of a blend of Lactobacillus acidophilus ATCC SD5221 and Bifidobacterium lactis ATCC SD5219 in patients with allergic rhinitis.MethodsA double-blind, randomized, cross-over study, involving 31 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…Prior to this study, the effect of NCC 2461 in modulating grass pollen allergic rhinitis was evaluated in two exploratory studies, outside the pollen season in nasal provocation test settings [ 12 , 13 ]. Results of these trials suggested a role of NCC 2461 in immune regulation, as cytokine expression by peripheral blood mononuclear cells cultures [ 12 ] or in nasal secretions [ 13 ] was significantly different when compared to a placebo [ 12 ] or a different probiotic blend [ 13 ]. In addition, both studies showed that NCC 2461 administration might affect distinct subjective symptoms of allergic rhinitis, namely congestion [ 12 ] and pruritus [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to this study, the effect of NCC 2461 in modulating grass pollen allergic rhinitis was evaluated in two exploratory studies, outside the pollen season in nasal provocation test settings [ 12 , 13 ]. Results of these trials suggested a role of NCC 2461 in immune regulation, as cytokine expression by peripheral blood mononuclear cells cultures [ 12 ] or in nasal secretions [ 13 ] was significantly different when compared to a placebo [ 12 ] or a different probiotic blend [ 13 ]. In addition, both studies showed that NCC 2461 administration might affect distinct subjective symptoms of allergic rhinitis, namely congestion [ 12 ] and pruritus [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Results of these trials suggested a role of NCC 2461 in immune regulation, as cytokine expression by peripheral blood mononuclear cells cultures [ 12 ] or in nasal secretions [ 13 ] was significantly different when compared to a placebo [ 12 ] or a different probiotic blend [ 13 ]. In addition, both studies showed that NCC 2461 administration might affect distinct subjective symptoms of allergic rhinitis, namely congestion [ 12 ] and pruritus [ 13 ]. In contrast, the results from the study presented in this manuscript indicate no effect of NCC 2461 in modulating TNSS, TOSS, nor any of the symptoms considered individually.…”
Section: Resultsmentioning
confidence: 99%
“…29 Notably, a recent study evidenced a clear Th2-Th1 shift and Treg induction in allergic patients treated with lactobacilli without improvement in allergic symptoms. 30 One possible explanation for the lack of clinical remission might be that lactobacilli evoke immune cellular responses that are allergen-independent and, therefore, not allergen-specific. This may hamper the clinical efficacy of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…53 A crossover RCT compared the effects of two oral probiotic preparations (a powdered form of L. paracasei NCC2461 versus a blend of L. acidophilus ATCC SD5221 and Bifidobacterium lactis ATCC SD 5219) in 28 adults with allergic rhinitis to grass pollen. 54 Subjects received each product for 4 weeks-separated by a washout period of 6-8 weeksfollowed by a nasal provocation test. In contrast to consumption of the L. acidophilus and B. lactis blend, treatment with L. paracasei significantly reduced nasal pruritus but not nasal congestion, associated with a decrease in nasal fluid leukocytes and secretions of several interleukins.…”
Section: Allergic Disordersmentioning
confidence: 99%